Lesson Study: professional development (PD) for beginning and experienced teachers. Issue 2 (15th March 2019) - Coenders, Fer; Verhoef, Nellie
Abstract: Central in this study is the professional development of beginning and experienced teachers collaborating in Lesson Study teams. Two high school teacher teams participated, a chemistry and a multidisciplinary team. Each team consisted of a beginning and an experienced teacher. Both teams went through the Lesson Study cycle twice. What and from what the beginning and experienced teachers learned, differences in teacher leaning and what Lesson Study elements contributed to this learning were studied in a qualitative multiple case study using interviews, reflective journals, and recordings . The Extended Interconnected Model for Professional Growth was used to interpret teacher learning. Our results show that two Lesson Study teams materialized in which participants shared experiences, thoughts, and ideas related to teaching and learning. Lesson Study contributed to both beginning and experienced teachers' PCK development. The combination of two phases in this professional development program proved instrumental for this PCK development: a development phase in which participants meet new pedagogies, discuss these in the perspective of student learning, design a lesson plan and prepare for class use. Followed by a class enactment phase where the designed lesson is enacted, students are observed, subsequently salient results are discussed and the lesson plan revised.